Inclusive Education in the Illusio Space. A Proposal to Research the School FIeld - Karolina Kołodziejczak (Journal of Vasyl Stefanyk Precarpathian National University)
This article describes planned research on the practice of inclusive education in Poland in the context of Pierre Bourdieu's [3] concept of society, in which field is one of the basic concepts. In using this term, the author intends to describe the social space of the school, the social space’s organization, and the state of the school’s social position; as well as to answer the question: What is the reality of inclusive education, as analyzed using the illusio category? It is necessary to analyze the state of the implementation of the assumptions made by inclusive education in primary schools, and to find out the opinions of teachers working with students covered by this type of education. In P. Bourdieu’s [3] concept of society, the field is the source of what is social, it shapes it in those who are within its area of influence. This “attitude” is called illusio [11, p. 188]. Illusio is a state of engrossment in a game that the participant is unaware of. This is the result of direct recognition of the field's requirements. Everyday educational life in the context of P. Bourdieu's concept falls within the field of activities of the Ministry of National Education. The teacher takes part in a game whose rules are set by the Ministry of National Education. In the context of the proposed research within the scope of the field, apart from teachers, there are also the parents of the children covered by inclusive education.